MENELUSURI KEDUDUKAN PANCASILA SEBAGAI SUMBER DARI SEGALA SUMBER HUKUM (Discovering the Position of Pancasila as the Basic Norm in Indonesia) - Wahanu Prabandani, Hendra (IBLAM LAW REVIEW, 2022)
The Constitution of Republic Indonesia is absent to describe Pancasila as the rule that forms an underlying basis for a legal system in Indonesia. It might become a problem when the majority number of statesmen is difficult to find a legal reference regarding Pancasila as the basic norm in Indonesia. This article aims to discover the position of Pancasila as the basic norm in statutory system in Indonesian, and how Pancasila is implemented in the construction of Indonesia legal system. Pancasila as the basic norm is reflected in the preambule of 1945 Constitution and in article 1 (3) of 1945 Constitution. Prior to the amendment of 1945 Constitution, explaination regarding Pancasila as a basic norm was stipulated in MPRS Decree XX/MPRS/1966 regarding Source of the Law Governance Republic Indonesia and Hieararchy of Law and Regulatin in Indonesia, also MPR Decree II/MPR-RI/1978 regarding Guidline of Implementation Pancasila or Eka Prasetya Pancakarsa. Furthermore, after the amendement of 1945 Constitution, Pancasila as the basic norm might be found in Law Number 12 Year 2011 regarding Establishment of Legislation and Presidential Regulation Number 87 Year 2014 regarding Implementation Regulation of Law Number 12 Year 2011 regarding Establishment of Legislation. The concept of Pancasila as the basic norm is implemented as micro aspect which is in the principle of statutory making, and macro aspec as the foundation of rule of law as well as legal development in Indonesia.